A REVIEW OF THE LINKAGE BETWEEN EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - M.YUSOF, HALIMAH; GAN, JENG LING (Human Sustainability Procedia, 2018)
This article reviewed the past studies that were conductedin the recent years(2010-2016) on the linkage between emotional intelligenceand organizational citizenship behaviour. Organizational citizenship behaviour has been recognized as the important element for an organization due to it can affect the effectiveness of the organization. It becomesthe concern in organizational behaviour studies and it has been used as dependent variable frequently. Emotional intelligence has potential influence onto organizational citizenship behaviour. However, there is a lack of attention onto the research of emotional intelligence, especially in Malaysia. Thus, this paperintends to highlight the needs to make further investigation on the linkage between these two variables. Some suggestions were provided for future studies